Efficacy of radiosensitizing doped titania nanoparticles under hypoxia and preparation of an embolic microparticle - Morrison RA (Dove Medical Press, 2017)
Rachel A Morrison,1,* Malgorzata J Rybak-Smith,1,* James M Thompson,2 Bénédicte Thiebaut,3 Mark A Hill,2 Helen E Townley1,4 1Department of Engineering Science, 2Gray Laboratories, CRUK/MRC Oxford Institute for Radiation Oncology, University of Oxford, Oxford, 3Johnson Matthey, Technology Centre, Reading, Berkshire, 4Nuffield Department of Obstetrics and Gynaecology, John Radcliffe Hospital, University of Oxford, Oxford, UK *These authors have contributed equally to this work Abstract: The aim of this study was to develop a manufacturing protocol for large-scale production of doped titania radiosensitizing nanoparticles (NPs) to establish their activity under hypoxia and to produce a multimodal radiosensitizing embolic particle for cancer treatment. We have previously shown that radiosensitizing NPs can be synthesized from titania doped with rare earth elements, especially gadolinium. To translate this technology to the clinic, a crucial step is to find a suitable, scalable, high-throughput method. Herein, we have described the use of flame spray pyrolysis (FSP) to generate NPs from titanium and gadolinium precursors to produce titania NPs doped with 5 at% gadolinium. The NPs were fully characterized, and their capacity to act as radiosensitizers was confirmed by clonogenic assays. The integrity of the NPs in vitro was also ascertained due to the potentially adverse effects of free gadolinium in the body. The activity of the NPs was then studied under hypoxia since this is often a barrier to effective radiotherapy. In vitro radiosensitization experiments were performed with both the hypoxia mimetics deferoxamine and cobalt chloride and also under true hypoxia (oxygen concentration of 0.2%). It was shown that the radiosensitizing NPs were able to cause a significant increase in cell death even after irradiation under hypoxic conditions such as those found in tumors. Subsequently, the synthesized NPs were used to modify polystyrene embolization microparticles. The NPs were sintered to the surface of the microparticles by heating at 230°C for 15 minutes. This resulted in a good coverage of the surface and to generate embolization particles that were shown to be radiosensitizing. Such multimodal particles could therefore result in occlusion of the tumor blood vessels in conjunction with localized reactive oxygen species generation, even under hypoxic conditions such as those found in the center of tumors. Keywords: cancer, ROS, reactive oxygen species, titania, multimodal